Improvement of loperamide-hydrochloride-induced intestinal motility disturbance by Platycodon grandiflorum polysaccharides through effects on gut microbes and colonic serotonin - Hao, Mengqi; Song, Jing; Zhai, Xiaohu; Cheng, Nuo; Xu, Cong; Gui, Shuangying; Chen, Juan (Frontiers in Cellular and Infection Microbiology, 2023)
Constipation is a common gastrointestinal symptom characterized by intestinal motility disorder. The effects of Platycodon grandiflorum polysaccharides (PGP) on intestinal motility have not been confirmed. We established a rat model of constipation induced by loperamide hydrochloride to elucidate the therapeutic effect of PGP on intestinal motility disorder and to explore the possible mechanism. After PGP treatment (400 and 800 mg/kg) for 21 d, PGP clearly relieved gastrointestinal motility, including fecal water content, gastric emptying rate, and intestinal transit rate. Moreover, the secretion of motility-related hormones, gastrin and motilin, were increased. Enzyme-linked immunosorbent assay, western blot, immunohistochemistry, and immunofluorescence results confirmed that PGP significantly increased the secretion of 5-hydroxytryptamine (5-HT) and the expression of related proteins, such as tryptophan hydroxylase 1, 5-HT4 receptor, and transient receptor potential ankyrin 1. 16S rRNA gene sequencing showed that PGP significantly increased the relative abundance of Roseburia, Butyricimonas, and Ruminiclostridium, which were positively correlated with 5-HT levels. However, the relative abundance of Clostridia_UCG-014, Lactobacillus, and Enterococcus were decreased. PGP improved intestinal transport by regulating the levels of 5-HT, which interacts with the gut microbiota and the intestinal neuro-endocrine system, further affecting constipation. Overall, PGP is a potential supplement for the treatment of constipation.